Attaching mass to the upper arm can increase throw distance in a modified javelin throw - Linthorne, N.; Heys, M.; Reynolds, T.; Eckardt, N. (Acta of Bioengineering and Biomechanics, 2020)
The effectiveness of the whip-like coordination in throwing might be influenced by the inertial properties of the athlete`s arm. This preliminary study investigated the acute effect of attaching mass to the upper arm on the distance achieved in a modified javelin throw.The aim was to identify the optimum upper arm mass that maximizes throw distance.Methods:Three well-trained adult male athletes performed maximum-effort throws with an 800-g javelin training ball. A wide range of masses (0-1.5 kg) were attached to the upper arm and a 2D video analysis was used to obtain measures of the projection variablesfor each attached mass. Results:All three athletes showed an effect of attached arm mass on throwdistance,and with the optimum mass the athlete`s throw distance was increased by 2.2m, 1.2m, and 0m (7%, 4%, and 0%)respectively. The optimum mass was specific to the athlete (0.6kg, 0.2kg, and 0 kg)and changes in throw distance were mostly due to changes in release velocityrather than changes in release angle or release height. Theexperimental results were broadly similar to those obtained from a simple 2D mathematical model of throwing. Conclusions:These results indicatethat some javelin throwersmight see an increase in throwing performance when a mass is attached to theirupper arm.However, the relationship between upper arm mass and throwing performance shouldbe investigated furtherwith studies on more athletes,projectiles of different mass, andother throwing events.